2018
DOI: 10.1371/journal.pone.0192010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms associated with psoriasis and development of psoriatic arthritis in patients with psoriasis

Abstract: BackgroundPsoriasis (PsO) is a chronic inflammatory disease with predominantly cutaneous manifestations. Approximately one third of patients with PsO develop psoriatic arthritis (PsA), whereas the remaining proportion of patients has isolated cutaneous psoriasis (PsC). These two phenotypes share common immunology, but with different heredity that might in part be explained by genetic variables.MethodsUsing a candidate gene approach, we studied 53 single nucleotide polymorphisms (SNPs) in 37 genes that regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 65 publications
0
28
0
1
Order By: Relevance
“…Most of the SNPs assessed in our study have known biological effects thus allowing a biological interpretation of the observed associations based on increased or reduced gene activity as summarised in Table and illustrated in Figure . Among patients with CD, the association observed for the TNFRSF1A (rs4149570) polymorphism indicates that increased expression of the TNF‐α receptor 1, and thus increased activity of the TNF‐α pathway, was associated with beneficial response.…”
Section: Discussionmentioning
confidence: 86%
“…Most of the SNPs assessed in our study have known biological effects thus allowing a biological interpretation of the observed associations based on increased or reduced gene activity as summarised in Table and illustrated in Figure . Among patients with CD, the association observed for the TNFRSF1A (rs4149570) polymorphism indicates that increased expression of the TNF‐α receptor 1, and thus increased activity of the TNF‐α pathway, was associated with beneficial response.…”
Section: Discussionmentioning
confidence: 86%
“…Most of the SNPs assessed in our study have known biological effects thus allowing a biological interpretation of the observed associations based on increased or reduced gene activity as summarized in Table 2 [ 35 47 ]. The associations observed for the TNF (rs1800629 and rs361525) polymorphisms suggest that reduced TNF-α mRNA level and expression of TNF-α was associated with reduced risk of AS [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are conflicting results about association between another polymorphism of TNFA gene (rs361525) and PS or PsA (Loft et al, 2018). The curative effect of TNF-α blockers in patients with PS and PsA indicates that, to a certain degree, they share common immunopathogenesis (Mease, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Approximately one third of patients with PS develop psoriatic arthritis (PsA), a chronic inflammatory heterogeneous disease that can affect various distinct anatomical sites including peripheral and axial joints, entheses, skin and nails. Both PS and PsA are T-cell-mediated autoimmune diseases united under the term of psoriatic disease (Baliwag et al, 2015;Loft et al, 2018;Sakkas and Bogdanos, 2017). Their pathogenesis is largely driven by the dysregulation of pro-inflammatory and anti-inflammatory cytokines production.…”
Section: Introductionmentioning
confidence: 99%